Struggling in Silence: The Effects of Deprivation on Social Behavior (International Journal of Food and Nutritional Sciences, 2022)
The present study examines how the Socio-economic-status is influencing on deprivation among the destitute in different age group, Bangalore with 300 samples from the various destitute centers. A random sampling method is used to collect the data. Valid and reliable SES scale and Deprivation scales measured the high, middle and low level of SES respectively. Keeping in the views of objectives and hypotheses of the study, Independent-test and One-way ANOVA statistical techniques were used.